2006
DOI: 10.1371/journal.ppat.0020060
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral DNA Integration: Viral and Cellular Determinants of Target-Site Selection

Abstract: Retroviruses differ in their preferences for sites for viral DNA integration in the chromosomes of infected cells. Human immunodeficiency virus (HIV) integrates preferentially within active transcription units, whereas murine leukemia virus (MLV) integrates preferentially near transcription start sites and CpG islands. We investigated the viral determinants of integration-site selection using HIV chimeras with MLV genes substituted for their HIV counterparts. We found that transferring the MLV integrase (IN) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
309
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(350 citation statements)
references
References 45 publications
31
309
1
9
Order By: Relevance
“…These integration pattern results have been confirmed and extended in two new studies that are described in more detail below [101,110]. Since IN is the viral determinant of retroviral targeting specificity [149], the data are consistent with the exclusive interaction of p75 with lentiviral IN proteins [75,87,100]. In vitro, chimeric lambda repressor-IBD proteins were also found to increase recombinant IN-mediated strand transfer near lambda repressor-binding sites in a DNA target [150].…”
Section: Viral Cofactor Rolesupporting
confidence: 64%
“…These integration pattern results have been confirmed and extended in two new studies that are described in more detail below [101,110]. Since IN is the viral determinant of retroviral targeting specificity [149], the data are consistent with the exclusive interaction of p75 with lentiviral IN proteins [75,87,100]. In vitro, chimeric lambda repressor-IBD proteins were also found to increase recombinant IN-mediated strand transfer near lambda repressor-binding sites in a DNA target [150].…”
Section: Viral Cofactor Rolesupporting
confidence: 64%
“…SC-1 cells transduced with GV vectors had a B1.7-fold higher MFI for eGFP and mCherry than their LV counterparts. As GV tend to integrate in the vicinity of promoters, DNaseI hypersensitive sites as well as CpG islands and LV within active transcription units, 53 the different expression levels observed for both vector families could reflect a better accessibility of transcription factors to the GV promoter/enhancer complex. The integration of bidirectional vectors within actively transcribed genes might be problematic considering that the cellular RNA running over the viral LTR boundaries will ultimately result in the formation of dsRNA that can trigger nuclear and cytoplasmic dsRNA responses and subsequent A-I editing of the message, reduced cap-dependent translation or cell death.…”
Section: Improving Bidirectional Vector Performancementioning
confidence: 99%
“…Thus, although integration site analysis can provide interesting data when malignancy arises from genetic modification, 45 it was unlikely to provide any meaningful data from the polyclonal populations of T cells in this study, as there would likely be many sites involved consistent with the largely random integration of retroviral vectors. 18 To realize the promise of gene therapy for the treatment of many diseases and disorders, there is a need for vectors with a demonstrated safety record for each particular application. We have demonstrated that despite the potential of Moloney murine leukemia virusbased vectors to lead to transformation of stem cell progeny in mice and humans, these vectors can be used with relative safety to genetically modify mature T cells.…”
Section: Absence Of Retroviral Transformation Of T Cells In Micementioning
confidence: 99%
“…[8][9][10] Retroviral vectors have also been used successfully in human trials to correct gene deficiencies in diseases including ADA-SCID, [11][12][13][14] X-linked SCID 15,16 and chronic granulomatous disease. 17 Retroviruses insert their genes in a semirandom manner into host chromosomes, 18 and it is thought that retroviruses may integrate preferentially into transcriptionally active sites. 19 There is therefore potential to dysregulate expression of genes including proto-oncogenes, which may lead to malignant transformation of gene-modified cells.…”
Section: Introductionmentioning
confidence: 99%